Timing of Sedimentary Evolution and Transgressions in the Bohai Sea During the Last ∼200 ka: Constraints from Luminescence Dating of a Core from the Yellow River Delta - Zhang, Xin; Liu, Jian; Wang, Yixuan; Chen, Tianyuan; Abbas, Mahmoud; Qian, Shengling (Frontiers in Earth Science, 2022)
The southwestern coast of the Bohai Sea is a favourable area to study land–sea interactions and palaeoenvironmental changes. The Bohai Sea hosts vast volumes of sediment discharged from rivers of mainland China and undergone large-scale sea-level fluctuations during the Quaternary. Three transgressions have been previously determined for the Bohai Sea since the Late Pleistocene. However, the timings of the two earlier transgressions are still unclear. Here we present chronological, micropalaeontological, and sedimentological data for an 80-m-long sediment core recovered from the modern Yellow River delta. The changes in grain size and foraminiferal assemblages suggest the occurrence of three marine sedimentary units, M-3, M-2 and M-1, that represent transgressions of the Bohai Sea. We applied optically stimulated luminescence dating using both quartz and feldspar minerals on fifteen samples obtained from core YRD-1401 and eight radiocarbon ages using fragments of microfossils shells and organic carbon. Our quartz optically stimulated luminescence ages for M-2 (ca. 60 ka), are consistent with K-feldspar post-infrared stimulated luminescence ages, suggesting that M-2 on the southwestern coast of the Bohai Sea deposited during early MIS 3. The sea level of the Bohai Sea during early MIS 3 is estimated to have ranged from 26.8 to 19.9 m below the present sea level. Luminescence ages and foraminiferal assemblages indicate that M-3 was likely formed during MIS 5 and a tidal-river environment prevailed in the southwestern coast of the Bohai Sea during MIS 6 or earlier.